Enrichment of CD44 in Exosomes From Breast Cancer Cells Treated With Doxorubicin Promotes Chemoresistance - Wang, Xiaohong; Cheng, Kai; Zhang, Guoqiang; Jia, Zhongming; Yu, Yue; Guo, Jiwei; Hua, Yitong; Guo, Fengli; Li, Xiaoqiang; Zou, Weiwei; Sun, Hongguang; Dong, Jianli; et al. (Frontiers in Oncology, 2020)
Exosomes secreted from tumor cells can remodel the tumor environment by promoting tumor metastasis and multidrug resistance. The aim of this study was to analyze the proteome profile of the breast cancer line resistant to doxorubicin resistance (MCF-7/ADR) by liquid chromatography linked to tandem mass spectrometry assay (LC-MS/MS). Our results revealed that DOX increases the exosomes release from MCF-7/ADR cells and the exosome-mediated proteins intercellular transfer in breast cancer chemoresistance regulation. The expression of the candidate target exosomic CD44 in DOX-resistant cells (A/Exo) was higher than in parental breast cancer cells (S/Exo), and the increasing levels of exosomic CD44 (21.65-fold) were higher than those of cellular CD44 (6.55-fold) (all p < 0.05). Similar results were obtained in clinical samples; exosomal CD44 in the serum of nonresponders was significantly higher than that in the chemotherapy-responsive group (p < 0.05). Also, we modified the MCF-7–derived exosomes loaded with siRNA against CD44 to observe the effects of targeting reduced CD44 expression in luminal A breast cancer cells. Exosome-siRNA targeted CD44 (Exos-siCD44) could efficiently silence its expression. When cocultured on Exos-siCD44, breast cancer cells exhibited reduced cell proliferation and enhanced susceptibility to DOX. The same phenomenon was observed in mice. In conclusion, breast cancer cells could spread resistance capacity by the intercellular transfer of proteins, especially CD44, via exosomes.